Public policy networks and the implementation of the Bolsa-Família Program: An analysis based on the monitoring of school attendance - Breynner Ricardo Oliveira; Doriana Daroit (Arizona State University, 2020)
The paper analyzes the connections derived from the routines and processes linked to the monitoring of school attendance of the Bolsa Família Program (BFP) in the city of Belo Horizonte. Based on the Actor Network Theory, the theoretical approach articulates technology, routines, street-level bureaucrats and the territory in the policy network materialized. Thirty-one multilevel public agents were interviewed, including 14 education professionals in two schools and eight social work professionals in two local centers. The analysis reveals that school attendance causes the social program to have a strong connection with education, promoting intersectoral and multilevel cooperation through the connection between school and social assistance centers in the territory. In addition, the results present a theoretical-methodological path for public policy network analysis.